2020
DOI: 10.1111/bph.15298
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption and hepatic elimination of drugs in high‐fat high‐cholesterol diet‐induced non‐alcoholic steatohepatitis rats: exemplified by simvastatin

Abstract: Background and Purpose: Altered drug pharmacokinetics is a significant concern in non-alcoholic steatohepatitis (NASH) patients. Although high-fat high-cholesterol (HFHC) diet-induced NASH (HFHC-NASH) rats could simulate the typical dysregulation of cholesterol in NASH patients, experimental investigation on the altered drug pharmacokinetics in this model are limited. Thus, the present study comprehensive investigates the nature of such altered pharmacokinetics using simvastatin as the model drug.Experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…During the 12‐week feeding, body weight gains of rats that fed with the HFHC diet (n = 6) were 496.3 ± 5.27 g and showed no significant difference with 501.3 ± 17.7 g of the rats fed the normal chow (n = 6) (Figure 1B). Meanwhile, significantly higher ALT, AST, LDL and total cholesterol levels, and lower HDL levels were observed in the rats that fed with the HFHC diet (Figure 1C), indicating the occurrence of liver injury and hyperlipidemia as described before 36,37 . H&E staining results in Figure 1D demonstrate severe hepatic steatosis, moderate inflammation in the hepatic lobule and a few ballooning degradations of hepatocytes in the HFHC‐NAFLD rats.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…During the 12‐week feeding, body weight gains of rats that fed with the HFHC diet (n = 6) were 496.3 ± 5.27 g and showed no significant difference with 501.3 ± 17.7 g of the rats fed the normal chow (n = 6) (Figure 1B). Meanwhile, significantly higher ALT, AST, LDL and total cholesterol levels, and lower HDL levels were observed in the rats that fed with the HFHC diet (Figure 1C), indicating the occurrence of liver injury and hyperlipidemia as described before 36,37 . H&E staining results in Figure 1D demonstrate severe hepatic steatosis, moderate inflammation in the hepatic lobule and a few ballooning degradations of hepatocytes in the HFHC‐NAFLD rats.…”
Section: Resultsmentioning
confidence: 56%
“…Meanwhile, significantly higher ALT, AST, LDL and total cholesterol levels, and lower HDL levels were observed in the rats that fed with the HFHC diet (Figure 1C), indicating the occurrence of liver injury and hyperlipidemia as described before. 36,37 H&E staining results in Figure 1D demonstrate severe hepatic steatosis, moderate inflammation in the hepatic lobule and a few ballooning degradations of hepatocytes in the HFHC-NAFLD rats. Those symptoms in rats could be identified as NAFLD.…”
Section: Hfhc-nafld Rat Model Establishmentmentioning
confidence: 93%
See 2 more Smart Citations
“…In line with this finding, Hardwick et al found an increased expression of P-gp in human liver samples with the progression of NAFLD [ 28 ]. Other studies have also demonstrated a higher hepatic P-gp expression, as well as lower AUC following intravenous and oral dosing of digoxin in rats with NAFLD [ 29 , 30 ]. Nevertheless, in the study by Abernethy et al, there was no difference in the clearance of digoxin between patients with obesity and normal weight controls following intravenous administration [ 31 ].…”
Section: Discussionmentioning
confidence: 99%